Isoterm Adsorpsi Ion Cr(III) Oleh Kitosan Hasil Isolasi Limbah Kepiting Rajungan dan Kitosan Komersil - Rahayu, Rahayu; Tanasale, Matheis F.J.D.P.; Bandjar, Adriani (Indonesian Journal of Chemical Research, 2020)
The chitin isolation from crab Rajungan (Portunus sanginolentus) and commercial chitin was done. The chitosan was made by deasetilation of chitin using alkaline solution with addition NaBH4. The chitin and chitosan were identified by related instrument. The identification by adsorption Cr(III) ion on chitosan was done by the Atomic Absorption Spectrofotometry. The result of the chitosan isolation was fitted to the Freundlisch isotherm, with KF = 1.18673 mg/g and 1/n= 0.2712.